SDGs 12 Needs Coastal Sustainability: Impact of Sand Mining Activities on Environmental Conditions in Kodingareng Lompo Island, Indonesia - Ketriyanti Agus; Agussalim Burhanuddin; Seniwati Seniwati (Fakultas Teknik Universitas Cenderawasih, 2024)
Sand mining in coastal regions, particularly on Kodingareng Lompo Island, has emerged as an environmental concern that profoundly affects ecosystem sustainability and the livelihoods of local populations. This study aims to analyze the impact of sand mining activities on coastal ecological conditions and their relationship to Sustainable Development Goal (SDG) 12 on sustainable consumption and production. A qualitative approach will be adopted, using interviews with local stakeholders such as fishermen, women entrepreneurs, the Neighborhood Association, and the Neighborhood Unit. Sand mining causes coastal erosion, habitat destruction, and water quality degradation. As a result, fishermen's catches and the economic incomes of local communities decline dramatically. This practice accelerates environmental damage contrary to the SDGs and exacerbates damage contrary to the principles of SDG 12. Recommendations for stricter regulations and implementing environmentally friendly mining methods can reduce adverse environmental impacts and support the sustainability of coastal ecosystems and the well-being of local communities. Such policies are essential to balance natural resource utilization and conservation efforts, aligning with SDG target 12. The novelty of this study lies in the need for more literature discussing this issue in Kodingareng Lompo Island.